Carbon-coated positive electrode material, positive electrode plate and battery
By covering the carbon layer on the positive electrode material of the lithium-ion battery and using sp3 hybrid carbon atoms to improve the ionic conductivity, the problems of side reactions and low ionic conductivity of traditional positive electrode materials are solved, and higher battery capacity and stability are achieved.
Patent Information
- Application Number
- CN202411651621.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-02-14
AI Technical Summary
The positive electrode material of traditional lithium-ion battery is prone to side reactions with the electrolyte material, and the ionic conductivity is low, limiting the further application of lithium-ion batteries.
The carbon-coated cathode material is used, which includes a core and a carbon coating layer. The carbon coating layer contains carbon atoms bonded in the sp3 hybrid way, and the intensity of the first peak position in the X-ray photoelectron spectroscopy test results and The intensity ratio of the second peak position is ≥0.1 to improve ionic conductivity and suppress side reactions between the positive electrode material and the electrolyte material.
It effectively improves the charge and discharge specific capacity and cycle stability of the battery, and reduces deterioration caused by contact between the positive electrode active material and the electrolyte material.
Smart Images

Figure CN119447259A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a carbon-coated positive electrode material, a positive electrode sheet and a battery. Background Art
[0002] A battery is a device that can store and release electrical energy. Lithium-ion batteries are currently the most widely used battery system in commercial applications. The positive electrode material of lithium-ion batteries is part of the composition of lithium-ion batteries and directly affects the performance of lithium-ion batteries. At present, traditional positive electrode materials are prone to side reactions with electrolyte materials and have low ion conductivity, which limits the further application of lithium-ion batteries. Summary of the invention
[0003] Based on this, it is necessary to provide a carbon-coated positive electrode material, a positive electrode plate and a battery. The carbon-coated positive electrode material can have high ion conductivity and can also suppress the side reaction between the positive electrode material and the electrolyte material.
[0004] In the first aspect, the present application provides a carbon-coated positive electrode material, comprising a core and a carbon coating layer, wherein the carbon coating layer is coated on the surface of the core; the material of the core comprises a doped or undoped positive electrode active material, wherein the positive electrode active material comprises one or more of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, layered ternary positive electrode material, spinel lithium nickel manganese oxide, lithium iron phosphate, lithium iron manganese phosphate, lithium manganese phosphate and lithium cobalt phosphate; the X-ray photoelectron spectroscopy test results of the carbon coating layer have the following characteristics: the carbon element has a first peak position corresponding to sp3 hybridization and a second peak position corresponding to sp2 hybridization, and the ratio of the intensity of the first peak position to the intensity of the second peak position is ≥0.1.
[0005] In some embodiments, in the X-ray photoelectron spectroscopy test results of the carbon coating layer, the carbon element has a composite peak between 284eV and 287eV formed by the superposition of the first peak position and the second peak position, and the composite peak is subjected to peak separation processing to form the first peak position between 284eV and 285eV and the second peak position between 285eV and 286eV, respectively.
[0006] In some embodiments, the carbon coating layer further includes oxygen element, and the X-ray photoelectron spectroscopy test results of the carbon coating layer also have the following characteristics: the oxygen element has peak positions between 530eV~532eV and 528eV~530eV.
[0007] In some embodiments, the carbon coating layer has a thickness of 1 nm to 100 nm.
[0008] In some embodiments, in the carbon-coated positive electrode material, the mass percentage of carbon element in the carbon-coated positive electrode material is 0.2% to 5%.
[0009] In some embodiments, the particle size of the core is 100 nm to 100 μm.
[0010] In a second aspect, the present application provides a positive electrode plate, comprising a current collector and an active layer located on at least one surface of the current collector, wherein the active layer comprises any of the carbon-coated positive electrode materials described above.
[0011] In some embodiments, the active layer further includes one or more of a conductive agent and a binder.
[0012] In a third aspect, the present application provides a battery comprising any of the above-mentioned positive electrode plates.
[0013] In some embodiments, the battery is a lithium-ion battery, a solid-state battery, or a semi-solid-state battery.
[0014] The above-mentioned carbon-coated positive electrode material includes a core and a carbon coating layer, and the carbon coating layer contains not only carbon atoms bonded in sp2 hybridization mode, but also carbon atoms bonded in sp3 hybridization mode. Compared with sp2 hybridized carbon atoms, the structure formed by carbon atoms bonded in sp3 hybridization mode is more solid, and the effect of carbon atoms bonded in sp3 hybridization mode on promoting ion conduction is more obvious. The use of a carbon coating layer with a ratio of the intensity of the first peak position to the intensity of the second peak position ≥ 0.1 can effectively avoid the deterioration caused by the contact between the positive electrode active material and the electrolyte material, and at the same time can also improve the ionic conductivity of the carbon-coated positive electrode material.
[0015] Experimental verification has shown that the use of this carbon-coated positive electrode material can effectively improve the battery's charge and discharge capacity and cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, drawings of other embodiments can be obtained based on these drawings without paying any creative work.
[0017] FIG1 is a schematic diagram of the steps of a method for preparing a carbon-coated positive electrode material;
[0018] FIG2 is a schematic diagram showing the morphology of the carbon-coated positive electrode material in Example 1 observed using a transmission electron microscope;
[0019] FIG3 is a curve after peak separation processing based on the X-ray photoelectron spectroscopy test results of the carbon-coated positive electrode material in Example 1;
[0020] FIG. 4 is an X-ray photoelectron spectroscopy test result of the carbon-coated positive electrode material of Comparative Example 1. DETAILED DESCRIPTION
[0021] In order to make the above-mentioned purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are described in detail below. In the following description, many specific details are set forth to facilitate a full understanding of the present application. However, the present application can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present application, so the present application is not limited by the specific embodiments disclosed below.
[0022] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application. The term "and / or" used herein includes any and all combinations of one or more of the related listed items.
[0023] In the description of the present application, it should be understood that the terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise", "axial", "radial", "circumferential" and the like indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present application and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the present application.
[0024] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Thus, a feature defined as "first" or "second" may explicitly or implicitly include at least one of the features. In the description of this application, "plurality" means at least two, such as two, three, etc., unless otherwise clearly and specifically defined.
[0025] In conventional technology, the material of the carbon coating layer used to coat the positive electrode material is usually an amorphous carbon material and / or a graphitized carbon material, wherein the carbon atoms in the graphitized carbon material are bonded in an sp2 hybridized manner, and the material shows a peak corresponding to the sp2 hybridization in the X-ray photoelectron spectroscopy test results. The graphitized carbon material has a high electrical conductivity, which is conducive to promoting the conduction of electrons.
[0026] An embodiment of the present application provides a carbon-coated positive electrode material, including a core and a carbon coating layer, wherein the carbon coating layer is coated on the surface of the core; the material of the core includes doped or undoped positive electrode active material, and the positive electrode active material includes one or more of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, layered ternary positive electrode material, spinel lithium nickel manganese oxide, lithium iron phosphate, lithium iron manganese phosphate, lithium manganese phosphate and lithium cobalt phosphate; the X-ray photoelectron spectroscopy test results of the carbon coating layer have the following characteristics: the carbon element has a first peak corresponding to sp3 hybridization and a second peak corresponding to sp2 hybridization, and the ratio of the intensity of the first peak to the intensity of the second peak is ≥0.1.
[0027] The above-mentioned carbon-coated positive electrode material includes a core and a carbon coating layer, and the carbon coating layer contains not only carbon atoms bonded in sp2 hybridization mode, but also carbon atoms bonded in sp3 hybridization mode. Compared with sp2 hybridized carbon atoms, the structure formed by carbon atoms bonded in sp3 hybridization mode is more solid, and the effect of carbon atoms bonded in sp3 hybridization mode on promoting ion conduction is more obvious. The use of a carbon coating layer with a ratio of the intensity of the first peak position to the intensity of the second peak position ≥ 0.1 can effectively avoid the deterioration caused by the contact between the positive electrode active material and the electrolyte material, and at the same time can also improve the ionic conductivity of the carbon-coated positive electrode material.
[0028] Experimental verification has shown that the use of this carbon-coated positive electrode material can effectively improve the battery's charge and discharge capacity and cycle stability.
[0029] It can be understood that in the X-ray photoelectron spectroscopy test results, the actual positions of the first peak corresponding to sp3 hybridization and the second peak corresponding to sp2 hybridization are related to the overall structure and composition of the material, which makes the actual positions of the first peak and the second peak different in different carbon coating layers. In addition, the first peak and the second peak may also form a composite peak due to partial overlap, but technicians can analyze the hybridization state corresponding to each peak from the X-ray photoelectron spectroscopy test results in combination with common knowledge in the field and technical means such as peak separation processing.
[0030] As an example of this embodiment, the ratio of the intensity of the first peak to the intensity of the second peak can be 0.1, 0.3, 0.5, 1, 2, 3, 5, 7, 10, 20, 30, 50, 100, or the ratio of the intensity of the first peak to the intensity of the second peak can be between any two of the above ratios.
[0031] It can be understood that the ratio of the intensity of the first peak to the intensity of the second peak herein may have no upper limit. For example, when the second peak is substantially absent in the carbon coating layer, the intensity ratio may be infinite.
[0032] In some of the embodiments, in the X-ray photoelectron spectroscopy test results of the carbon coating layer, the carbon element has a composite peak between 284eV and 287eV formed by the superposition of a first peak and a second peak. After peak separation, the composite peak forms a first peak between 284eV and 285eV and a second peak between 285eV and 286eV.
[0033] In some of the embodiments, the carbon coating layer further includes oxygen element, and the X-ray photoelectron spectroscopy test results of the carbon coating layer also have the following characteristics: the oxygen element has peaks between 530eV~532eV and 528eV~530eV.
[0034] During the research process, the present application discovered that when the carbon coating layer contains oxygen element and has peaks between 530eV~532eV and 528eV~530eV, the carbon-coated positive electrode material has better ion conductivity.
[0035] In some embodiments, the thickness of the carbon coating layer is 1 nm to 100 nm.
[0036] The carbon coating layer within this thickness range can take into account both good protection and the role of promoting ion conduction. When the thickness of the carbon coating layer is too large, the excessively thick carbon coating layer may block the normal transmission of ions. Optionally, the thickness of the carbon coating layer is 2nm~20nm. Further optionally, the thickness of the carbon coating layer can be 2nm, 3nm, 4nm, 5nm, 7nm, 10nm, 12nm, 15nm, 17nm or 20nm, or the thickness of the carbon coating layer can also be within the range between any two of the above thicknesses.
[0037] In some of the embodiments, in the carbon-coated positive electrode material, the mass percentage of carbon element in the carbon-coated positive electrode material is 0.2% to 5%.
[0038] In the range of the mass percentage of the carbon element in the carbon-coated positive electrode material, the carbon coating layer can take into account both good protection and the role of promoting ion conduction. Optionally, in the carbon-coated positive electrode material, the mass percentage of the carbon element in the carbon-coated positive electrode material is 0.2%, 0.5%, 0.8%, 1%, 1.5%, 2%, 3%, 4% or 5%, or, in the carbon-coated positive electrode material, the mass percentage of the carbon element in the carbon-coated positive electrode material can also be in the range between any two of the above mass percentages.
[0039] In some embodiments, the particle size of the core is 100 nm to 100 μm.
[0040] Optionally, the particle size of the inner core is 100nm, 500nm, 1μm, 5μm, 10μm, 15μm, 20μm, 30μm, 40μm, 50μm, 60μm, 70μm, 80μm, 90μm or 100μm, or, the particle size of the inner core can also be within the range between any two of the above particle sizes.
[0041] Another embodiment of the present application also provides a method for preparing a carbon-coated positive electrode material, which includes the step of forming a carbon coating layer on the surface of a core.
[0042] Fig. 1 is a schematic diagram of the steps of a method for preparing a carbon-coated positive electrode material. Referring to Fig. 1 , the method for preparing a carbon-coated positive electrode material includes the following steps S1 to S2.
[0043] Step S1, providing a core, the core material includes doped or undoped positive electrode active materials, the positive electrode active materials include one or more of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, layered ternary positive electrode materials, spinel lithium nickel manganese oxide, lithium iron phosphate, lithium iron manganese phosphate, lithium manganese phosphate and lithium cobalt phosphate.
[0044] Step S2, forming a carbon coating layer on the surface of the inner core.
[0045] In some embodiments, the step of preparing and forming the carbon coating layer includes: mixing a carbon source precursor with the inner core, and calcining the mixture by microwave heating in a protective gas to form a carbon coating layer on the surface of the inner core.
[0046] Among them, compared with the usual heating method of heat conduction, calcination by directly heating the carbon source precursor with microwaves can transform the carbon source precursor into sp3 hybridized carbon elements, so that the carbon elements in the carbon coating layer have sp3 hybridized components.
[0047] As an example of this embodiment, the protective gas should be selected from gases that do not react with the carbon source precursor and the core. In some examples, the protective gas is selected from one or more of argon and nitrogen.
[0048] In some embodiments, during the calcination by microwave heating, the mixed material can be controlled to be heated by microwave to 180° C. to 1500° C.
[0049] It is understandable that for different carbon source precursors, the heating temperature may be different, and the specific temperature should be based on the structure of the carbon coating layer to be generated. The heating temperature can be controlled by controlling the power of the microwave.
[0050] Optionally, during the process of calcining by microwave heating, the mixed material can be controlled to be heated by microwave to 500° C. to 700° C. Further optionally, during the process of calcining by microwave heating, the mixed material can be controlled to be heated by microwave to 500° C., 520° C., 550° C., 570° C., 600° C., 620° C., 650° C., 670° C., 700° C., or, during the process of calcining by microwave heating, the mixed material can be controlled to be heated by microwave to a temperature within the range between any two of the above temperatures.
[0051] In some embodiments, the mixed material can be controlled to be heated by microwave for 2h to 8h.
[0052] Optionally, the time for the mixed material to be heated by microwaves can be controlled to be 2h, 3h, 4h, 5h, 6h, 7h, or 8h, or the time for the mixed material to be heated by microwaves can be controlled to be within the range between any two of the above times.
[0053] It can be understood that by controlling the temperature and heating time of microwave heating, the intensity ratio of the first peak and the second peak in the formed carbon coating layer can be correspondingly controlled.
[0054] In some of the embodiments, the mass ratio of the carbon source precursor to the core is 1:(0.1~10).
[0055] Optionally, the mass ratio of the carbon source precursor to the core is 1:0.1, 1:0.2, 1:0.5, 1:0.8, 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9 or 1:10, or, the mass ratio of the carbon source precursor to the core can also be within the range between any two of the above mass ratios.
[0056] In some embodiments, the carbon source precursor includes one or more of phenolic resin, furfural resin, epoxy resin, urea-formaldehyde resin, asphalt, citric acid, glucose, sucrose, polyvinyl chloride, and polyvinyl butyral.
[0057] In some embodiments, the step of preparing the carbon coating layer comprises:
[0058] The inner core is arranged in a deposition chamber, a carbon source gas is introduced into the deposition chamber, and a carbon coating layer is deposited on the surface of the inner core by direct photochemical vapor deposition or plasma enhanced chemical vapor deposition.
[0059] Among them, compared with the usual thermal decomposition deposition method, the deposition method of direct photochemical vapor deposition or plasma enhanced chemical vapor deposition can make the carbon atoms produced by decomposition form sp3 hybrid bonds, so that the carbon elements in the carbon coating layer have sp3 hybrid components.
[0060] It can be understood that by controlling the light intensity during the photochemical vapor deposition process and the RF power during the plasma enhanced chemical vapor deposition process, the intensity ratio of the first peak and the second peak in the formed carbon coating layer can be correspondingly controlled.
[0061] In some of the embodiments, a protective gas is further introduced into the deposition chamber.
[0062] The protective gas should be selected from gases that do not react with the carbon source precursor and the electrolyte core.
[0063] In some embodiments, the protective gas is selected from one or more of argon and nitrogen.
[0064] In some of the embodiments, during the deposition process, the ambient temperature in the deposition chamber may be controlled to be between 180° C. and 1500° C.
[0065] In some of the embodiments, the ambient temperature in the deposition chamber may be controlled to be 500° C. to 700° C.
[0066] Optionally, the ambient temperature in the deposition chamber can be controlled to 500°C, 520°C, 550°C, 570°C, 600°C, 620°C, 650°C, 670°C, or 700°C, or, the ambient temperature in the deposition chamber can be controlled to be within the range between any two of the above temperatures.
[0067] In some of the embodiments, the deposition time can be controlled to be 1 h to 10 h.
[0068] Optionally, the deposition time can be controlled to be 1 h, 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h or 10 h, or the deposition time can be controlled to be within the range between any two of the above times.
[0069] In some embodiments, the carbon source gas includes one or more of acetylene, ethylene, methane, ethane, propane and n-butane.
[0070] In some of the embodiments, the flow rate of the carbon source gas introduced into the deposition chamber may be 0.1 L / min to 10 L / min.
[0071] Optionally, the flow rate of the carbon source gas introduced into the deposition chamber can be 0.1L / min, 0.2L / min, 0.5L / min, 0.8L / min, 1L / min, 2L / min, 3L / min, 4L / min, 5L / min, 6L / min, 7L / min, 8L / min or 10L / min, or, the flow rate of the carbon source gas introduced into the deposition chamber can be within the range between any two of the above flow rates.
[0072] Another embodiment of the present application provides a positive electrode plate, including a current collector and an active layer located on at least one surface of the current collector, wherein the active layer includes any of the above-mentioned carbon-coated positive electrode materials.
[0073] In some embodiments, the active layer further includes one or more of a conductive agent and a binder.
[0074] In some embodiments, the conductive agent may be selected from one or more of conductive carbon black, carbon nanotubes, graphene, and carbon nanofibers.
[0075] In some of the embodiments, the binder may be selected from one or more of polyvinyl pyrrolidone, polyvinylidene fluoride, polyethylene oxide, polytetrafluoroethylene, carboxymethyl cellulose and a copolymer of styrene and butadiene.
[0076] Another embodiment of the present application provides a battery, comprising any of the above-mentioned positive electrode sheets.
[0077] In some of these embodiments, the battery is a lithium-ion battery, a solid-state battery, or a semi-solid-state battery.
[0078] In some embodiments, the battery includes a positive electrode sheet, a negative electrode sheet, and a separator disposed between the positive electrode sheet and the negative electrode sheet.
[0079] In some embodiments, the negative electrode sheet includes a negative electrode current collector and a negative electrode active layer disposed on the negative electrode current collector, and the negative electrode active layer includes a negative electrode active material.
[0080] In some examples, the negative electrode active material includes one or more of graphite, silicon, silicon carbon, metallic lithium and lithium titanate. In addition, silicon-based materials may also be included. The silicon-based material may include one or more of elemental silicon, silicon-oxygen compounds, silicon-carbon composites, silicon-nitrogen composites and silicon alloys. In some specific examples, the silicon-based material uses silicon-oxygen materials or pre-lithiated silicon-oxygen particles.
[0081] In some examples, the negative electrode active layer may further include one or more of a conductive agent and a binder.
[0082] In the negative electrode active layer, the conductive agent may be selected from one or more of conductive carbon black, carbon nanotubes, graphene and carbon nanofibers.
[0083] In the negative electrode active layer, the binder may be selected from one or more of polyvinyl pyrrolidone, polyvinylidene fluoride, polyethylene oxide, polytetrafluoroethylene, carboxymethyl cellulose and a copolymer of styrene and butadiene.
[0084] In order to facilitate understanding of the specific implementation methods and beneficial effects of the present application, the present application also provides the following more specific examples and comparative examples. Through the description of the examples and comparative examples, the beneficial effects of the present application will also be more obvious.
[0085] Example 1
[0086] Preparation of carbon-coated positive electrode material: A layered nickel-cobalt-manganese ternary positive electrode material with a particle size of 1 μm is used as the core, and it is mixed evenly with sucrose at a mass ratio of 10:1 to form a mixed material. The mixed material is transferred to a microwave sintering chamber, and the microwave sintering chamber is kept in an argon atmosphere. The mixed material is heated to 650°C and calcined for 2 hours by microwave, and then cooled to room temperature to form a carbon-coated positive electrode material.
[0087] Preparation of positive electrode sheet: The carbon-coated positive electrode material, polyvinylidene fluoride and SuperP are uniformly mixed in a mass ratio of 95:3:2 and dispersed in nitrogen-methyl pyrrolidone to form a slurry. The slurry is coated on the surface of aluminum foil and then dried to form a positive electrode sheet.
[0088] Preparation of electrolyte: A mixed solvent of EC, DMC and FEC was used, wherein the volume ratio of EC, DMC and FEC was 4.8:4.8:0.4, and lithium hexafluorophosphate was dissolved in the mixed solvent, and the molar concentration of lithium hexafluorophosphate was 1 mol / L.
[0089] Preparation of battery: The above-mentioned positive electrode plate and lithium plate are assembled in pairs to form a half-battery, and the positive electrode plate and the lithium plate are separated by a Celgard2300 isolation film.
[0090] Example 2
[0091] The difference between Example 2 and Example 1 is only the preparation process of the carbon-coated positive electrode material. The preparation process of the carbon-coated positive electrode material in Example 2 is as follows: a layered nickel-cobalt-manganese ternary positive electrode material is placed in a direct photochemical vapor deposition chamber, acetylene with a flow rate of 1 L / min is introduced as a carbon source gas, the temperature of the deposition chamber is controlled to be 700° C., and the deposition time is 4 hours. After completion, it is cooled to room temperature to form a carbon-coated positive electrode material.
[0092] Example 3
[0093] The difference between Example 3 and Example 1 is only the preparation process of the carbon-coated positive electrode material. The preparation process of the carbon-coated positive electrode material in Example 3 is as follows: a layered nickel-cobalt-manganese ternary positive electrode material is placed in a plasma enhanced chemical vapor deposition chamber, acetylene with a flow rate of 1 L / min is introduced as a carbon source gas, the temperature of the deposition chamber is controlled to be 700° C., and the deposition time is 4 hours. After completion, it is cooled to room temperature to form a carbon-coated positive electrode material.
[0094] Example 4
[0095] The only difference between Example 4 and Example 1 is that Example 4 uses lithium iron phosphate as the core.
[0096] Example 5
[0097] The only difference between Example 5 and Example 1 is that Example 5 uses lithium iron manganese phosphate as the core.
[0098] Comparative Example 1
[0099] The only difference between Comparative Example 1 and Example 1 is that: Comparative Example 1 does not prepare carbon-coated positive electrode materials, and layered nickel-cobalt-manganese ternary positive electrode materials are used to replace the carbon-coated positive electrode materials in Example 1 when preparing positive electrode plates.
[0100] Comparative Example 2
[0101] The difference between Comparative Example 2 and Example 1 is only in the preparation process of the carbon-coated positive electrode material. In the preparation of the carbon-coated positive electrode material in Comparative Example 2, microwave radiation heating is not used, but heat conduction heating is performed by a resistance furnace.
[0102] Comparative Example 3
[0103] The only difference between Comparative Example 3 and Example 2 is the preparation process of the carbon-coated positive electrode material. In the preparation of the carbon-coated positive electrode material in Comparative Example 3, a conventional tube furnace is used for deposition instead of a direct photochemical vapor deposition chamber.
[0104] The morphology of the carbon-coated positive electrode material in Example 1 was observed using a transmission electron microscope. The morphology of the carbon-coated positive electrode material can be seen in FIG2 .
[0105] The carbon-coated positive electrode materials of Example 1 and Comparative Example 1 were tested by X-ray photoelectron spectroscopy, and the results can be seen in Figures 3 and 4. Figure 3 is a curve after peak separation based on the X-ray photoelectron spectroscopy test results of the carbon-coated positive electrode material of Example 1. Figure 4 is the X-ray photoelectron spectroscopy test results of the carbon-coated positive electrode material of Comparative Example 1.
[0106] 2 , it can be determined based on the observation results of the transmission electron microscope that there is an obvious carbon coating layer on the surface of the positive electrode material product prepared in Example 1, and the thickness of the carbon coating layer is less than 10 nm, specifically about 3 nm.
[0107] Further, referring to Figure 3, the abscissa in Figure 3 represents binding energy, and the ordinate represents intensity. After the peak separation process, the X-ray photoelectron spectroscopy test results of Example 1 have a first peak between 284eV and 285eV, and the intensity of the first peak is recorded as C1, and a second peak between 283eV and 284eV, and the intensity of the second peak is recorded as C2. The first peak corresponds to sp3 hybridized carbon elements, and the second peak corresponds to sp2 hybridized carbon elements. Obviously, the ratio of the intensity of the first peak C1 to the intensity of the second peak C2 is about 1.4. This shows that there are more sp3 hybridized carbon elements in the carbon coating layer prepared in the preparation process of Example 1.
[0108] As shown in Figure 4, the X-ray photoelectron spectroscopy test results of Comparative Example 1 show only one peak, corresponding to the sp2 hybridized carbon element. This indicates that the carbon coating layer prepared in the preparation process of Comparative Example 1 only has sp2 hybridized carbon elements, and basically does not have sp3 hybridized carbon elements.
[0109] The batteries of the above embodiments and comparative examples were tested for charge and discharge cycles, and the test results can be seen in Table 1.
[0110] Table 1
[0111]
[0112] As shown in Table 1, Comparative Example 1 did not prepare a carbon coating on the surface of the inner core, and directly added the layered ternary positive electrode material to the positive electrode plate. After 100 cycles, the cycle capacity retention rate of the battery was only 82.3%. Compared with Example 1, the initial discharge specific capacity of Comparative Example 2 is lower, and the cycle capacity retention rate is also lower. Combined with the differences in its preparation process and XPS test results, it can be seen that the difference in the results is mainly due to the fact that the carbon elements in the carbon coating in Comparative Example 2 are mainly sp2 hybridized. This shows that the ion conductivity and structural stability of the carbon coating formed by carbon atoms bonded in an sp2 hybridized manner are not as good as those of the carbon coating formed by carbon atoms bonded in an sp3 hybridized manner.
[0113] Example 2 and Example 3 respectively adopt photochemical deposition and plasma enhanced chemical vapor deposition to prepare the carbon coating layer, and the XPS test results of the products prepared are similar to those of Example 1. The prepared carbon coating layers contain more carbon elements bonded in the sp3 hybridization mode. Therefore, Example 2 and Example 3 can obtain initial discharge specific capacity and cycle capacity retention rate similar to that of Example 1.
[0114] In Example 4, lithium iron phosphate is used as the core, and similar specific capacity and capacity retention rate as those in Example 1 can be obtained. In Example 5, lithium iron manganese phosphate is used as the core. Due to the properties of the lithium iron manganese phosphate material itself, its initial discharge specific capacity is low, but a higher cycle capacity retention rate can still be achieved compared with the comparative example.
[0115] Please note that the above embodiments are for illustrative purposes only and are not meant to be limiting of this document.
[0116] It should be understood that, unless otherwise specified herein, there is no strict order restriction for the execution of the steps, and the steps may be executed in other orders. Moreover, at least a portion of the steps in the preparation process may include multiple sub-steps or multiple stages, and these sub-steps or stages are not necessarily executed at the same time, but may be executed at different times, and the execution order of these sub-steps or stages is not necessarily sequential, but may be executed in turn or alternately with other steps or at least a portion of the sub-steps or stages of other steps.
[0117] The various embodiments in this specification are described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the various embodiments can be referenced to each other.
[0118] The technical features of the above embodiments may be combined arbitrarily. To make the description concise, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
Claims
1. A carbon-coated positive electrode material, characterized in that: It comprises an inner core and a carbon coating layer, wherein the carbon coating layer is coated on the surface of the inner core; the material of the inner core comprises a doped or undoped positive electrode active material, wherein the positive electrode active material comprises one or more of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, layered ternary positive electrode material, spinel lithium nickel manganese oxide, lithium iron phosphate, lithium iron manganese phosphate, lithium manganese phosphate and lithium cobalt phosphate; the X-ray photoelectron spectroscopy test results of the carbon coating layer have the following characteristics: the carbon element has a first peak position corresponding to sp3 hybridization and a second peak position corresponding to sp2 hybridization, and the ratio of the intensity of the first peak position to the intensity of the second peak position is ≥0.
1.
2. The carbon-coated positive electrode material according to claim 1, characterized in that In the X-ray photoelectron spectroscopy test results of the carbon coating layer, the carbon element has a composite peak between 284eV and 287eV formed by the superposition of the first peak position and the second peak position. After peak separation processing, the composite peak forms the first peak position between 284eV and 285eV and the second peak position between 285eV and 286eV respectively.
3. The carbon-coated positive electrode material according to claim 1, characterized in that: The carbon coating layer also includes oxygen element, and the X-ray photoelectron spectrum test results of the carbon coating layer also have the following characteristics: the oxygen element has peak positions between 530eV~532eV and 528eV~530eV.
4. The carbon-coated positive electrode material according to any one of claims 1 to 3, characterized in that The thickness of the carbon coating layer is 1 nm to 100 nm.
5. The carbon-coated positive electrode material according to any one of claims 1 to 3, characterized in that: In the carbon-coated positive electrode material, the mass percentage of carbon element in the carbon-coated positive electrode material is 0.2% to 5%.
6. The carbon-coated positive electrode material according to any one of claims 1 to 3, characterized in that: The particle size of the core is 100nm~100μm.
7. A positive electrode sheet, characterized in that: It comprises a current collector and an active layer located on at least one surface of the current collector, wherein the active layer comprises the carbon-coated positive electrode material according to any one of claims 1 to 6.
8. The positive electrode sheet according to claim 7, characterized in that: The active layer further includes one or more of a conductive agent and a binder.
9. A battery, characterized in that: Including the positive electrode sheet as described in claim 7 or 8.
10. The battery according to claim 9, characterized in that The battery is a lithium-ion battery, a solid-state battery or a semi-solid-state battery.
Citation Information
Patent Citations
Positive electrode active material and preparation method thereof, positive electrode plate, battery and electric device
CN116897444A
Nitrogen-doped carbon-coated lithium iron phosphate positive electrode material as well as preparation method and application thereof
CN117317184A
Carbon-coated solid electrolyte, battery and electric equipment
CN118825456A
Positive active material for rechargeable lithium battery, and positive active material layer and rechargeable lithium battery including same
US20160099464A1